Radiological and clinical findings in uveal melanoma treated by plaque interventional radiotherapy (brachytherapy): Visual atlas and literature review on response assessment - Fionda, Bruno; Pagliara, Monica Maria; Lancellotta, Valentina; Caputo, Carmela Grazia; Casà, Calogero; Sammarco, Maria Grazia; Placidi, Elisa; Cornacchione, Patrizia; Boselli, Francesco; Iezzi, Roberto; Colosimo, Cesare; Tagliaferri, Luca; et al. (Journal of Contemporary Brachytherapy, 2022)
Uveal melanoma (UM) is the most common intra-ocular tumor in Caucasian adults and may derive from melanocytes. Historically, the first therapeutic approach to treat UM has been surgical removal of the eye, with obvious consequences in terms of function, cosmesis, and psychological impact on patients. Collaborative Ocular Melanoma Study (COMS) introduced the first uniform approach to perform interventional radiotherapy (IRT – brachytherapy) procedure in a standardized way that allowed to demonstrate equivalence of IRT with enucleation in terms of overall survival. Since this milestone, several international guidelines have been issued with regard to several technical aspects of this procedure, which has become the mainstream therapy worldwide. However, nowadays, there is still a lack of consensus about the criteria to definitively assess UM response after IRT. We present a collection of paradigmatic cases treated in our institution, and then discuss in detail the latest available evidence on the topic.